Pengaruh Stres Kerja, Motivasi Kerja, dan Disiplin Kerja terhadap Karyawan - Nada Kamiliya; Ahmad Gunawan (CV. Ulil Albab Corp, 2023)
The reason for this examination is to decide (1) the impact of work weight on representative execution, (2) the impact of work inspiration on representative execution, (3) the impact of work discipline on worker execution, (4)) to decide the effect of work weight on worker execution. ( 4) the impact of the three factors on representative execution; This examination is quantitative exploration. Quantitative examination is an exploration strategy that concentrates on a specific populace or test utilizing research techniques in view of representative information from the Sudhiroprajan Locale Office. The finish of this examination is: The t test shows that work pressure, work inspiration, and work discipline together impact representative execution. Since the judgment test results were 64.8%, it tends to be inferred that the capacity of the responsibility, work inspiration and work discipline factors to further develop representative execution was 64.8%. Work pressure is the most prevailing variable of the two factors which impacts representative execution factors.